Are data available for tracking progress on nutrition policies, programs, and outcomes in Maldives? - Neupane, Sumanta; Jangid, Manita; Scott, Samuel P.; Nguyen, Phuong Hong; Kim, Sunny S.; Murira, Zivai; Torlesse, Harriet; Menon, Purnima (International Food Policy Research Institute, 2021)
The World Health Organization (WHO) and other global nutrition and health agencies recommend nutrition actions across the life-course to address malnutrition in all its forms. In this report, we examined how Maldives’ nutrition policies and programs addressed recommended nutrition actions, determinants, and outcomes. We reviewed population-based surveys and assess the availability of data on nutrition actions, nutrition outcomes, and the determinants of these outcomes. Our review identified a total of 53 recommended evidence-based nutrition actions; of these, 49 nutrition actions were applicable in Maldives and 31 were addressed in the country’s nutrition policies and programs. The Maldives nutrition plan (the Integrated National Nutrition Strategic Plan, or INNSP) recognized and addressed all key determinants of nutrition except women’s status (appropriate age of marriage/childbirth) and infectious diseases; the country’s nutrition plan aimed to track progress on all nutrition outcome indicators. Our data review found that of 31 actions addressed by policies and programs, population-based surveys contained data on only 22 actions. Neither of the population-based surveys contained data on a range of actions, including advice on consuming iron and folic acid (IFA) during pregnancy, support for early initiation of breastfeeding and immediate skin-to-skin contact, optimal feeding of low-birth-weight infants, counseling of mothers of low-birth-weight infants on kangaroo mother care (KMC) during delivery and postpartum period, counseling on infant and young child feeding (IYCF), growth monitoring, and counseling after growth monitoring during early childhood. The population-based surveys contained data on most of the indicators for immediate and underlying determinants; indicators that were not available included maternal dietary diversity during pregnancy, household food insecurity, and coverage under social protection schemes. With the exception of anemia among non-pregnant women, data on all nutrition outcomes was available in population-based surveys. In conclusion, Maldives should consider updating its national policies and programs to address existing gaps in recommended nutrition actions; in addition, future population-based surveys may also need to be revised to fill identified data gaps around nutrition actions and determinants.